Syrian sumac (Rhus coriaria L.) - An effective medicinal plant against multidrug resistant uropathogenic Escherichia coli - Razan Marouf, Andrey Ermolaev, Irina Podoprigora, Elena Volina, Anna Zhigunov (Journal of Applied Pharmaceutical Science, 2022)
Urinary tract infections (UTIs) are a global concern causing annual health and economic burdens, especially with the massive prevalence of resistant uropathogens. In recent decades, medicinal plants have gained increasing attention as a promising alternative to traditional antibiotics. In this study, the antibacterial activity of the hydroalcoholic sumac extract was tested on clinical Uropathogenic Escherichia coli (UPEC) isolates including multidrug resistance strains. In the well diffusion method, sumac was effective against all bacteria in a concentration-dependent manner with an inhibition diameter of 7–15 mm for UPEC and 17–23 mm for the reference strain. Minimum inhibitory concentration/minimum bactericidal concentration were of 3.125/3.125–6.25 mg/ml for UPEC and 0.0244/1.563 mg/ ml for the reference strain. The extract reduced the hemagglutination of bacteria with human RBCs in all positive cases. Moreover, the extract inhibited the ability of UPEC to adhere to polystyrene surfaces at percentages of 79.1%– 95.1%. However, the extract did not affect the morphology of bacteria except for one isolate where it resulted in cell elongation and formation of short filaments. Long exposure to the extract did not reduce the sensitivity of the bacteria to it. Accordingly, sumac represents a promising natural antibacterial agent for the development of based pharmaceuticals to treat and prevent UTIs caused by UPEC.
Keywords: Uropathogenic Escherichia coli, urinary tract infections, sumac, Rhus coriaria, antibacterial agent, antibiotic resistance